Review: Modelling of Meniscus of Knee Joint During Soccer Kicking - Mohd Azrul Hisham, Mohd Adib; Mohd Firdaus, Jaafar (2013)
Knee is a part of the body that located between thigh and shank is one of the most complicated and largest joints in the human body. The common injuries that occur are ligaments, meniscus or bone fracture. During soccer games, the knee is the most critical part that will easily injure due to the shock from an external impact. Torn meniscus is one of the effects. This study will investigate the effect towards the meniscus within the knee joint during soccer ball kicking. We conduct a literary review of 14 journals that discuss the general view of meniscus and also soccer kicking. The selected topics for this review paper are meniscal function, meniscal movement, meniscal tears and also instep kick. As a finding, statistics show that most meniscal tears (73%) occurred in athletes who were soccer players, basketball players or skiers. The tear is frequently happening at the medial side rather than lateral side with a percentage of 70%.